"An Opening Toward the Possible": Assembly Politics and Henri Lefebvre's Theory of the Event. Issue 2 (2nd April 2020) - Jerrems, Ari
ABSTRACT: In this article, I outline how Henri Lefebve's theory of the event helps conceptualise the emergence of recent assembly movements. Scholars of time and temporality have critiqued conventional framings of events, instead often understanding these as ruptures in temporal narratives. Moving beyond the deconstruction of framings of events, several scholars have begun to engage with the contested forms of timing and rhythm emerging from them. Lefebvre's theory provides tools to build on this approach in order to conceptualise the event of assembly politics. Lefebvre's theory furthers the turn to timing by highlighting the interrelationship between space and time and engaging with the complex "totality" from which movements emerge. Lefebvre's theory provides a framework to track how seemingly micropolitical phenomena emerges from and reverberates on a worldwide scale. The insights gained from Lefebvre's theory are illustrated through an analysis of the emergence of the 15M movement in Spain.